Looking at architecture with humour. CAU and Focho: From the ‘ligne claire’ to the hermetic cartoon (1979-1982) - Tárrago Mingo, Jorge; Villanueva, María (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The intersections between architecture and humour are numerous. As part of social reality, architecture and the architect are the subject of satire in the same media in which public opinion deals with any other event. Humour can also be found in architectural theory and practice in different ways. However, it is not so common to find cartoons in architecture magazines in a stable way. The article exposes and analyzes the little-known case of the regular collaboration of the architect Justo Isasi, known as ’Focho’ for CAU magazine between 1979 and 1982. Through archive material and an interview with Focho, the article shows the changes in his drawings and proposes how looking at architecture through the prism of graphic humor takes us away from its most orthodox reading and from a perspective that, being caricatured, is nonetheless more precise and lucid about the debates of the period.